Dietary glycine protects from chemotherapy-induced hepatotoxicity - Mikalauskas, Saulius; Mikalauskiene, Laura; Bruns, Helge; Nickkholgh, Arash; Hoffmann, Katrin; Longerich, Thomas; Strupas, Kestutis; Büchler, Markus W.; Schemmer, Peter (Amino acids, 2011)
Hepatotoxic side effects of neoadjuvant chemotherapy for colorectal liver metastases increase perioperative morbidity and mortality. Glycine protects liver from injury in various animal models. Thus, this study was designed to assess its effect on liver after chemotherapy. Sprague-Dawley rats (200-220 g) were fed a synthetic diet containing 5% glycine for 5 days. Subsequently, chemotherapy (FOLFIRI: irinotecan, folinic acid and fluorouracil, or FOLFOX: oxaliplatin, folinic acid and fluorouracil) was administered at standard doses. Transaminases, histology, immunohistochemistry and in vivo microscopy were used to index liver injury, to monitor intrahepatic microperfusion and activation of Kupffer cells. Glycine significantly decreased transaminases after chemotherapy to 25-50% of control values (p < 0.05). Microvesicular steatosis was significantly reduced from 18.5 ± 3.4 and 57.1 ± 8.6% in controls to 9.5 ± 1.8 and 37.7 ± 4.4% after FOLFIRI and FOLFOX, respectively. Furthermore, phagocytosis of latex beads was reduced by about 50%, while leukocyte adherence in central and midzonal subacinar zones decreased to 60-80% after glycine (p < 0.05). Glycine significantly reduced expression of inducible nitric oxide synthase after chemotherapy, while hepatic microcirculation was increased (p < 0.05). This study shows for the first time that glycine reduces chemotherapy-induced liver injury. The underlying mechanisms most likely include Kupffer cells and an improved intrahepatic microperfusion.
Published online: 18 September 2010
Gesehen am 19.08.2022